Laparoscopic Management of Bouveret’s Syndrome after Failed Endoscopic Approach - Ariel Nicolas Tchercansky; Guido Luis Busnelli; Matías E. Mihura; Rafael José Maurette (Case Reports in Surgery)
Bouveret’s syndrome is a complication of cholelithiasis that presents with gastric outlet obstruction due to an impacted gallstone in the duodenum following cholecystoduodenal fistula. This is a rare presentation of biliary-enteric fistula; therefore, there are no standardized guidelines for the management of this disease. We present a case of a patient with Bouveret’s syndrome managed with laparoscopic surgery after an unsuccessful attempt of endoscopic removal.